Assessment of physical and mental well-being among students of Bangladesh during COVID-19 Pandemic - Shaha, Aurpita; Sarker, Mintu; Islam, Md. Nazmul; Khatun, Trishna; Bashir, Md. Abdul; Hossain, Md. Shamim (International Multidisciplinary Research Journal, 2021)
The outburst of COVID-19 influenced the lives of all segment of society as people were requested to self-quarantine in their homes to stop the outspread of the virus. The lockdown had consequential impacts on mental health, triggering psychological problems encompassing frustration, stress, and depression. The outbreak of Covid-19 has significantly affected the lives of all parts of the society. One of the most instant changes launched was the closure of educational institutions to decelerate the spreading of the virus. Students no longer had availability of institution-based physical activities such as physical education, recess, and walking to/from universities/colleges/school. Inadequate physical activities and enormous sedentary behavior amid students exhibits a noteworthy problem because health behavior patterns can result in heightened risk for a number of hazardous health conditions (e.g., overweight/obesity, type II diabetes, and metabolic syndrome) in later. The objective of this study was to explore the pervasiveness of physical and mental health condition among Bangladeshi students during the COVID-19 pandemic. It also focuses on recognizing the stimulus of various states of physical and mental conditions throughout COVID-19 pandemic. The cross sectional data was gathered by means of interviews or self-responses among the university students from various districts of Bangladesh on July to August 2020. The study was performed with structured questionnaire. To reduce threats of Covid-19 infection, in this investigation, participants were interviewed over telephone instead of face to face interaction. In order to explore the effects of this pandemic on the lives of students, we performed a survey in which a total of 576 participants were participated. In this survey, among them 377 (66%) are male and 197 (34%) female. It was discovered that 92% of participants appreciate participating in physical activities & rest of them (8%) don’t like to participate in physical activities. In addition, our study also revealed 46% of the students having trouble in sleep and 45% students feels concentration problem. The findings of this study show that greater numbers of the students are not in sound physical or mental conditions. They are bored, helpless, anxious and depressed than previous. This study shows that the mental conditions of female students are more affected by Covid-19 compared to male students. 82% of female students are stressed about their study, future life and so on. 46% female students are feeling helpless, 61% become upset and 60% feel bored during lockdown and close of education institution. COVID-19 is striking threat both on physical and mental health since its outbreak. During this challenging time, it is necessary to continue taking care of physical and mental health.